Advanced Structure-activity Relationships Applied to Mentha spicata L. Subsp spicata Essential Oil Compounds as AChE and NMDA Ligands, in Comparison with Donepezil, Galantamine and Memantine - New Approach in Brain Disorders Pharmacology - Avram, Speranta; Mernea, Maria; Bagci, Eyup; Hritcu, Lucian; Borcan, Livia-Cristina; Mihailescu, Dan Florin (Bentham Science Publ, 2017)
Background: Alzheimer's disease (AD) therapy is based on several natural and synthetic compounds that act as acetylcholinesterase (AChE) and N-methyl-D-aspartate receptor (NMDA) ligands that have limited efficiency in relieving AD symptoms. Recent studies show that inhibitors isolated from Mentha spicata L. subsp. spicata are promising for AD therapy. Objective: We aimed to identify novel and more potent phytopharmaceutical compounds for AD treatment by taking into account the compounds from Mentha spicata L. subsp. spicata essential oil. Method: We generated structure-activity relationship (SAR) models that predict the biological activities of 14 Mentha spicata L. subsp. spicata compounds on AChE and NMDA by comparing their molecular features with those of the three conventional ligands: donepezil, galantamine and memantine. Results: The most relevant descriptors for predicting the biological activities of considered compounds are solvent accessible area and their subdivided, hydrophobicity, energy of frontier molecular orbitals and counts of the aromatic ring and rotatable bounds. 1,8-cineole, the main compound from Mentha spicata L. subsp. spicata essential oil, resulted to be similar with memantine and dissimilar with donepezil in respect to hidrophobicity (logP(1),(8-cineole)=2.95, logP(memantine)=2.81, logP(donepezil)=4.11), the energy of LUMO (eLUMO(1,8-cineole)=3.01 eV, eLUMO(memantine)=3.35 eV, eLUMO(donepezil)=-0.35 eV) and the solvent accessible surface areas over all hydrophobic (SA_ H-1,H-8-cineole=350 angstrom(2), SA_ H-memantine=358 angstrom(2), SA_ H-donepezil=655 angstrom(2)) or polar atoms (SA_ P-1,P-8-cineole=4 angstrom(2), SA_ P-memantine=10 angstrom(2), SA_ P-donepezil=44.62 angstrom(2)). Conclusion: Our results point towards 1,8-cineole as a good candidate for NMDA antagonism, with a weaker AChE inhibitory effect. Our results may be useful in establishing new therapeutic strategies for neurological disorders.
Keywords: Acetylcholinesterase; Alzheimer's disease; 1,8-cineole; Mentha spicata L. subsp spicata essential oil; N-methyl-D-aspartate receptor; structure-biological activity relation